Pengaruh Efikasi Diri dan Komunikasi Interpersonal Terhadap Kinerja Pegawai Honorer Pada Dinas Pendidikan Pemuda dan Olahraga Kabupaten Solok - Shinta Ramadanis; Netti Indrawati; Afni Yeni (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to analyze the effect of Self-Efficacy and Interpersonal Communication on the performance of honorary Employees at the Solok District Youth and Sports Education Office. The sample in this study was 33 respondents based on gender, age, level of education. Based on the results of multiple linear regression analysis of self-efficacy and interpersonal communication variables on employee performance with a value of Y = 17.379 + 0.520 X1 + 0.074 X2 + e. From the t test conducted on variable X1, namely self-efficacy with a Tcount value greater than Ttable 3.196> 2.042, which means that the Self-Efficacy variable affects Honorary Employee Performance, as for the X2 variable, namely interpersonal communication, the Tcount score is less than Ttable 0.581 <2.042 which means Interpersonal Communication has no effect on Honorary Employee Performance. While the results of the f-test analysis obtained that the value of fcount is greater than ftable, namely 11.579> 3.32, which means that Self-Efficacy and Interpersonal Communication jointly affect the Performance of Honorary Employees.